APORTACIONES A LA HISTORIA DE LA TRANSMISIÓN DE LA CONSOLATIO AD LIVIAM - Bellido Díaz, José Antonio (Exemplaria Classica, 2015)
After some questions relating to an edition of Consolatio ad Liuiam, we present for the first time two new excerpts and an incunable which edits it, and restore a conjecture to its rightful author.